Energy transition and agro-wind productive lands in the commune of Negrete, Chile - Alarcón-Barrueto, Esteban (2025)
Introduction: Over the past decades, energy transition has emerged as a widely accepted global objective, predominantly driven by “market mechanisms” and capitalist innovation. Objective: Facing the risks of a post-fossil society that may reproduce and deepen current impacts and forms of domination, this article aims to analyze how green capitalism is territorialized through the implementation of wind farms in Negrete, as part of Chile's energy transition. Methodology: the study employed a qualitative approach, based on document and public policy analysis, along with 29 semi-structured interviews with key actors. Conclusions: the research identified the utilization of production conditions linked to the rural and agricultural configuration of the territory, based on what is termed "the ideal of agro-wind productive lands”. This territorialization coincides with a decline in small-scale farming, which, alongside land leasing dynamics, regulatory gaps, and exclusionary institutions, creates conditions highly favorable to the domination and control of space by companies. Consequently, local inhabitants not only begin to see themselves as powerless subjects but also change their perception of the state and companies, now characterized by distrust and discontent.